Mechanism of Neutrophil p90RSK-Nrf2 Signaling Pathway in Atherosclerosis - Jiawen Li; Lei Wang; Xiao Liang; Xiaoxia Li (Balkan Medical Journal, 2025)
Background: MRP8/14, a calcium-binding protein of the S100 family, is predominantly expressed in myeloid cells and exhibits proinflammatory and prothrombotic properties. Platelet-neutrophil interactions can trigger MRP8/14 release, but their role in atherosclerosis (AS) remains unclear. Aims: To investigate the effect of MRP8/14 on AS progression and the underlying mechanisms involved, focusing on neutrophil activation and the toll-like receptor 4 (TLR4)-ERK1/2-p90RSK and NRF2-ARE pathways. Study Design: Ex vivo and animal study. Methods: Neutrophils isolated from mouse bone marrow were stimulated with P-selectin to induce MRP8/14 release, which was subsequently quantified using ELISA. Neutrophil extracellular traps (NET) formation was induced by phobolol 12-myristate 13-acetate, and Mrp8/14 expression was examined via fluorescence labeling. Cytokine release and CD11b expression were assessed using flow cytometry. An AS mouse model was established by administering a high-fat diet. Atherosclerotic plaque size was analyzed using Oil Red O staining. Proteins from the TLR4-ERK1/2-p90RSK and NRF2-ARE pathways were analyzed by Western blotting. Results: P-selectin induced MRP8/14 release, which was inhibited by P-selectin antagonists. NET formation also contributed to MRP8/14 secretion. hMRP8/14 treatment enhanced CD11b expression, neutrophil adhesion, and proinflammatory cytokine secretion. In AS mice, MRP8/14 secretion was linked to TLR4 upregulation, ERK1/2-p90RSK signaling activation, and NRF2-ARE pathway inhibition. Paquinimod, an MRP8/14 antagonist, mitigated neutrophil activation, inflammation, and arterial plaque formation. Conclusion: MRP8/14 secreted from neutrophils activates the ERK1/2-p90RSK pathway via TLR4 and suppresses the NRF2-ARE pathway, driving inflammation and promoting AS progression.